2003
DOI: 10.1215/s1522851702000170
|View full text |Cite
|
Sign up to set email alerts
|

Neurolymphomatosis

Abstract: The term "neurolymphomatosis" (NL) has included infiltration of the peripheral nervous system by lymphoma and nontumor lymphocytes. We describe NL as a lymphoma entity that affects cranial and peripheral nerves and roots. We reviewed the medical records of patients at the Massachusetts General Hospital (MGH) who registered between 1972 and 2000, as well as cases published in the English-language literature. Inclusion criteria were (A) histopathologic demonstration of lymphoma within peripheral nerve, nerve roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
127
1
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(132 citation statements)
references
References 69 publications
1
127
1
3
Order By: Relevance
“…Treatment with intravenous high-dose methotrexate was initiated, but the Discussion NL is a rare but well-described entity, in which malignant lymphocytes infiltrate the peripheral nervous system (PNS) [4]. Although NL would appear to be the least common neurologic manifestation of lymphoma, Baehring et al [2] estimated that NL represents 10% of primary lymphomas of the nervous system (0.2% of all NHLs). Furthermore, between 8.5 and 29% of NHLs metastasize to the nervous system, and an estimated 10% of these involve the PNS [2].…”
Section: Case Reportmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment with intravenous high-dose methotrexate was initiated, but the Discussion NL is a rare but well-described entity, in which malignant lymphocytes infiltrate the peripheral nervous system (PNS) [4]. Although NL would appear to be the least common neurologic manifestation of lymphoma, Baehring et al [2] estimated that NL represents 10% of primary lymphomas of the nervous system (0.2% of all NHLs). Furthermore, between 8.5 and 29% of NHLs metastasize to the nervous system, and an estimated 10% of these involve the PNS [2].…”
Section: Case Reportmentioning
confidence: 99%
“…Although NL would appear to be the least common neurologic manifestation of lymphoma, Baehring et al [2] estimated that NL represents 10% of primary lymphomas of the nervous system (0.2% of all NHLs). Furthermore, between 8.5 and 29% of NHLs metastasize to the nervous system, and an estimated 10% of these involve the PNS [2].…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurolymphomatosis (NL) also is a rare manifestation of non-Hodgkin lymphoma in which lymphoma cells infiltrate the peripheral nerves. 12,13 NL is characterized clinically by a painful polyneuropathy or polyradiculopathy, cranial neuropathy, painless polyneuropathy, and peripheral mononeuropathy. Unfortunately, the diagnosis of NL often is difficult and requires histologic confirmation of the affected nerve, which may not be feasible and often is nondiagnostic.…”
mentioning
confidence: 99%
“…Unfortunately, the diagnosis of NL often is difficult and requires histologic confirmation of the affected nerve, which may not be feasible and often is nondiagnostic. 12,14 Enhanced magnetic resonance imaging (MRI) is useful in diagnosing NL before histopathologic confirmation by revealing the enlargement and enhancement of the affected nerve, although it may not always provide optimal visualization of lymphomatous involvement. 12,15 Several recent studies have demonstrated the advantages of FDG-PET/CT in the diagnosis of NL.…”
mentioning
confidence: 99%